Alcohol in older people: systematic reviews of interventions and context. (November 2016) - Kelly, Sarah; Olanrewaju, Olawale; Cowan, Andy; Brayne, Carol; Lafortune, Louise
Abstract: Background: Harmful alcohol consumption is increasing in older people because of an ageing population and heavier consumption in the generation now reaching older age. This work was part of a comprehensive evidence synthesis of preventive health behaviour interventions to inform policy and identify evidence gaps relating to ageing well and cognitive health. Methods: Three systematic reviews in older populations were done to identify interventions to prevent or reduce excessive alcohol consumption, to identify the same type of interventions that also report cognitive and dementia outcomes, and to identify barriers and facilitators. Treatment for alcohol dependence was excluded. Multiple databases (Medline, Embase, PsycINFO, CINAHL, CENTRAL, Social Sciences Citation Index, and grey literature) were searched for studies published from 2000 in English, from Organisation for Economic Co-operation and Development countries. MeSH terms and text words relating to alcohol consumption and behaviour were used combined with older age terms (appendix ). Risk of bias was assessed with National Institute for Health and Care Excellence methodology. Findings: 12 intervention studies targeting prevention or reduction of excessive alcohol consumption and 11 qualitative studies reporting barriers and facilitators were identified, but none with cognitive or dementia outcomes. Only three studies related to prevention; and nine aimed to reduce alcohol in harmful or hazardous drinkers in primary care. A complex range of intervention types, intensity, and delivery was found. Five studies that compared one type of intervention with another or compared more intensive interventions with minimal intervention found no differences, although both groups markedly reduced alcohol consumption. Limited evidence (three studies) suggested that more intensive interventions that include personalised feedback could have the greatest effects in older hazardous drinkers. However, some evidence suggested that simple interventions including brief interventions, leaflets, and alcohol assessments with advice to reduce drinking can also have a positive effect. From qualitative studies, drinking in some older people was strongly linked to social engagement and enjoyment of life and there was scepticism about the health risks of alcohol. Conversely, drinking was also linked to difficulties such as social isolation, stress, illness, or bereavement. Emphasis on the experience of older people to drink wisely in a positive controlled way could be a facilitator. Interpretation: Alcohol interventions in older people can be effective. Messages might need to consider the impact on social engagement in light of potential benefits of social participation for cognitive health. Funding: National Institute for Health Research (NIHR) School for Public Health Research and NIHR Collaboration for Leadership in Applied Health Research East of England.